Evaluation of pharmaceutical pictogram comprehension among adults in the Philippines - Margarita M. Gutierrez; Chanthawat Patikorn; Puree Anantachoti (Taylor & Francis Group, 2022)
Background The use of pharmaceutical pictograms to enhance patients' understanding of drug regimens has been proven effective in many countries. There are two reference systems for pictograms generally used in pharmacy: the United States Pharmacopeia (USP) and International Pharmacy Federation (FIP). This study aimed to evaluate the effectiveness of USP and FIP pictograms among adults in the Philippines by identifying how many pictograms would pass the American National Standards Institute (ANSI) criterion of 85% comprehension, and to describe the factors affecting pictograms' comprehension. Methods A descriptive cross-sectional research using a face-to-face interview was performed to evaluate 108 pictograms in 52 Filipino adults enrolled through quota sampling. Descriptive statistics, Mann-Whitney U test (Wilcoxon rank-sum test), univariate linear regression, and multiple linear regression were used to statistically analyze the data collected. Results Only 17 (16 USP and 1 FIP) out of the 108 pictograms (15.74%) passed the ANSI criterion. The median score of Filipinos was 71 out of 108 pictograms (Interquartile range: 10-96). The multivariate model (R 2 = 0.5645, F (4,47) = 15.23) suggested that the score was lower by 5.85 points if the user was female, 21.58 points lower if the participant was below Grade 12 education level, and 1.20 points lower if the patient was greater than 46 years old. Education level was identified as the significant predictor (p-value < 0.0000*, power = 99.98%). The participant with greater than Grade 12 has a higher comprehension score of rank-sum 952.5 (Expected = 689) compared to only 425.5 (Expected = 689). Conclusions Since only 17 pictograms passed as stand-alone tool for patient information material, the researchers recommend the use of verbal and written instructions to complement pictograms to enhance comprehension. Furthermore, the government should consider the inclusion of health pictograms in basic health education.